Language Use and International Business: What Can We Learn from Anthropology? - Lauring, Jakob; Bjerregaard, Toke (HERMES - Journal of Language and Communication in Business, 2007)
This article addresses the role of language use in international business. It argues that the impact of linguistic differences on the daily workings of international business activities and communication is shaped by the way in which these differences intersect with the social and professional structures of international ﬁrms. Thus, the analysis of management across linguistic variation requires an understanding of the character of the social and professional ties in which international business is embedded. The intensity of cross-linguistic challenges in international management is not given by the formal character and structure of linguistic differences only. While the daily practices of language use in an international ﬁrm are shaped by its social and professional structure, linguistic practices may also strengthen the social and professional ties shaping the dissemination of information. The role of linguistic differences in everyday business communication both shapes and is shaped by the character of social and professional groupings and networks in an international ﬁrm. For management, this means that handling linguistic variation and challenges also requires a consideration of the speciﬁc social as well as professional structure of a given international ﬁrm. The dynamics between language use and the social structures in which information and resources are embedded and communicated are multidirectional. This is especially clear in an international context. The article is informed by material obtained through an ethnographic ﬁeldwork in a Saudi-Arabian subsidiary of a multinational corporation.